THE SECRET LIVES OF FORESTS: A DESCRIPTIVE STUDY OF PLANT COMMUNITIES AND ECOSYSTEM DYNAMICS - Zakir Hussain Mir; Irshad Ahmad Wani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Forests, often referred to as the "lungs of the Earth," are complex ecosystems composed of diverse plant communities that interact with each other and the environment in dynamic ways. This paper provides a descriptive study of forest plant communities and ecosystem dynamics, focusing on the intricate processes that shape the structure, function, and sustainability of these ecosystems. By examining key ecological concepts such as plant-pollinator relationships, nutrient cycling, competition, succession, and symbiosis, this study sheds light on the unseen, yet essential, interactions within forest ecosystems. Understanding these dynamics is crucial for the conservation and management of forests, especially in the face of anthropogenic pressures. The research emphasizes the importance of plant communities in maintaining ecosystem balance and highlights the critical role of forests in global biodiversity and climate regulation.